Cardiovascular biomarkers in paired maternal and umbilical cord blood samples at term and near term delivery. (March 2016) - Blohm, Martin E.; Arndt, Florian; Sandig, Jan; Diehl, Werner; Zeller, Tanja; Mueller, Goetz C.; Schlesner, Claudia; Mir, Thomas S.; Blankenberg, Stefan; Hecher, Kurt; Singer, Dominique; Weil, Jochen
Abstract: Background: Cardiovascular biomarkers might help to identify fetuses or pregnancies at risk. Aim: To examine the umbilical cord neonatal and maternal levels of cardiovascular biomarkers at the time of delivery, and to correlate maternal and fetal biomarker levels to each other, to gestational age and to delivery mode. Study design: In a prospective, observational, cross-sectional, single-center study biomarkers were measured in paired maternal and umbilical venous cord blood samples. Subjects: The sample cohort included 66 sets of fetal and maternal blood samples (11 after multiple gestation, 53 after cesarean section, 17 after exposure to labor). Outcome measures: Midregional pro-adrenomedullin (MRproADM), midregional-pro atrial natriuretic peptide (MRproANP), brain natriuretic peptide (BNP), n-terminal-pro brain natriuretic peptide (NTproBNP), copeptin, and high sensitive troponin I (hsTnI) levels were measured. Results: Mean ± SEM for biomarker levels in umbilical venous/maternal blood were: MRproADM [nmol/L] 1.02 ± 0.04/1.24 ± 0.08, MRproANP [pmol/L] 215.53 ± 12.96/54.65 ± 3.41, BNP [pg/mL] 32.02 ± 3.37/19.76 ± 3.29, NTproBNP [pg/mL] 1228.94 ± 91.73/71.48 ± 8.65, copeptin [pmol/L] 103.42 ± 22.89/10.41 ± 1.71, and hsTnI [pg/mL] 13.54 ± 5.17/4.91 ± 2.37. Fetal MRproANP, NTproBNP, and BNP were inversely correlated with gestational age. Maternal and fetal MRproANP ( r  = 0.472, p  = 0.002) and copeptin ( r  = 0.572, p  < 0.001) levels were correlated, whereas there was no feto-maternal correlation for the other biomarkers. Fetal copeptin was elevated after exposure to labor. Conclusions: Biomarker levels appear to be regulated independently in mother and fetus. Fetal biomarkers are influenced by gestational age and delivery mode. In this study on term and near term pregnancies without specific fetal pathology, correlation between paired maternal and fetal biomarker levels was weak or not demonstrable. Highlights: Cardiovascular biomarker levels were measured in paired maternal and umbilical cord blood samples. Biomarker levels of MRproANP, BNP, NTproBNP and copeptin were significantly higher in fetal than in maternal blood. Gestational age and labor did influence biomarker levels. Fetal and maternal levels of MRproANP and copeptin were weakly correlated.